2009
DOI: 10.1007/s12098-009-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in children with steroid-sensitive nephrotic syndrome

Abstract: Bone mineral density in steroid sensitive nephrotic syndrome is unaffected by cumulative dose of prednisolone therapy both in first episode as well as relapser group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
1
26
1
Order By: Relevance
“…[7,19,20] However, other studies have reported that cumulative steroid dose does not affect bone density in steroid-sensitive NS patients. [21,22] Similarly, we did not find a statistically significant difference between the cumulative dose of steroid and bone density.…”
Section: Discussioncontrasting
confidence: 54%
“…[7,19,20] However, other studies have reported that cumulative steroid dose does not affect bone density in steroid-sensitive NS patients. [21,22] Similarly, we did not find a statistically significant difference between the cumulative dose of steroid and bone density.…”
Section: Discussioncontrasting
confidence: 54%
“…The values of E, Z, ∆S and ∆G estimated by Coats-Redfern method are presented in Table 2. The value of ∆S is large and negative and small value of Z suggests that the transition state is in highly ordered state than individual reactant and it is a rate-determining step [27,28]. The kinetic parameters show a somewhat different trend from that of thermal stability.…”
Section: Kinetics Of Decompositionmentioning
confidence: 92%
“…They have exhibited antitumorogenic activity by reducing the number and size of carcinogen induced colon tumors and play synergistic role on the activity of certain antitumor drugs, although the mechanism has not been completely clarified [31][32][33]. Ligands having nitrogen donors received considerable attention because of their mixed hard-soft donor character, versatile coordination behavior [34][35] and for their biological activity (i.e., toxicity against bacterial growth [36], anticancer [37] and other biochemical properties [38]). The coordination geometry and nature of donor atoms play key roles in determining the binding extent of complexes to DNA.…”
Section: Introductionmentioning
confidence: 99%